Anthocyanins Protect Hepatocytes against CCl4-Induced Acute Liver Injury in Rats by Inhibiting Pro-inflammatory mediators, Polyamine Catabolism, Lipocalin-2, and Excessive Proliferation of Kupffer Cells - Dejan Popović; Gordana Kocić; Vuka Katić; Aleksandra Zarubica; Ljubinka Janković Veličković; Vanja P. Ničković; Andrija Jović; Andrej Veljković; Vladimir Petrović; Violeta Rakić; Zorica Jović; Nataša Poklar Ulrih; et al. (Antioxidants, 2019)
This study examined the hepatoprotective and anti-inflammatory effects of anthocyanins from Vaccinim myrtillus (bilberry) fruit extract on the acute liver failure caused by carbon tetrachloride-CCl4 (3 mL/kg, i.p.). The preventive treatment of the bilberry extract (200 mg anthocyanins/kg, orally, 7 days) prior to the exposure to the CCl4 resulted in an evident decrease in markers of liver damage (glutamate dehydrogenase, sorbitol dehydrogenase, malate dehydrogenase), and reduced pro-oxidative (conjugated dienes, lipid hydroperoxide, thiobarbituric acid reactive substances, advanced oxidation protein products, NADPH oxidase, hydrogen peroxide, oxidized glutathione), and pro-inflammatory markers (tumor necrosis factor-alpha, interleukin-6, nitrite, myeloperoxidase, inducible nitric oxide synthase, cyclooxygenase-2, CD68, lipocalin-2), and also caused a significant decrease in the dissipation of the liver antioxidative defence capacities (reduced glutathione, glutathione S-transferase, and quinone reductase) in comparison to the results detected in the animals treated with CCl4 exclusively. The administration of the anthocyanins prevented the arginine metabolism’s diversion towards the citrulline, decreased the catabolism of polyamines (the activity of putrescine oxidase and spermine oxidase), and significantly reduced the excessive activation and hyperplasia of the Kupffer cells. There was also an absence of necrosis, in regard to the toxic effect of CCl4 alone. The hepatoprotective mechanisms of bilberry extract are based on the inhibition of pro-oxidative mediators, strong anti-inflammatory properties, inducing of hepatic phase II antioxidant enzymes (glutathione S-transferase, quinone reductase) and reduced glutathione, hypoplasia of Kupffer cells, and a decrease in the catabolism of polyamines.